1999
DOI: 10.1046/j.1471-4159.1999.0720238.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood—Brain Barrier Glucose Transporter

Abstract: Abstract:The transport of glucose across the blood-brain barrier (BBB) is mediated by the high molecular mass (55-kDa) isoform of the GLUT1 glucose transporter protein. In this study we have utilized the tritiated, impermeant photolabel 2-N-[4-(1-azi-2,2,2-trifluoroethyl)[2-3 H]propyl]-1,3-bis(D-mannose-4-yloxy)-2-propylamine to develop a technique to specifically measure the concentration of GLUT1 glucose transporters on the luminal surface of the endothelial cells of the BBB. We have combined this methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
2
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(98 citation statements)
references
References 44 publications
5
90
2
1
Order By: Relevance
“…and sglt1 in cerebENDs after OGD and reoxygenation on the protein level (see supplementary figure 1) supporting our glucose uptake results and confirming data from the literature that glucose transporters are posttranscriptionally regulated by processes which can control mRNA stability, transporter concentrations at the luminal surface and their affinities to glucose [6,21]. Furthermore, presence and function of other glucose transporters at the BBB should not be neglected.…”
Section: Resultssupporting
confidence: 91%
“…and sglt1 in cerebENDs after OGD and reoxygenation on the protein level (see supplementary figure 1) supporting our glucose uptake results and confirming data from the literature that glucose transporters are posttranscriptionally regulated by processes which can control mRNA stability, transporter concentrations at the luminal surface and their affinities to glucose [6,21]. Furthermore, presence and function of other glucose transporters at the BBB should not be neglected.…”
Section: Resultssupporting
confidence: 91%
“…␥-glutamyltranspeptidase and System A amino acid transport activity with N-(methylamino)isobutyric acid as substrate, respectively (8). Rat microvessels and vascular-free rat brain membranes were prepared as previously described (15,16).…”
Section: Methodsmentioning
confidence: 99%
“…␥-glutamyltranspeptidase and System A amino acid transport activity with N-(methylamino)isobutyric acid as substrate, respectively (8). Rat microvessels and vascular-free rat brain membranes were prepared as previously described (15,16).Western Blot-Western blot analysis was performed as previously described (17) and quantified by chemiluminescence and image analysis (18). Human erythrocyte and rat brain membrane samples were included on all blots as internal GLUT1 standards for quantitation.…”
mentioning
confidence: 99%
“…It has been shown that both acute and chronic (both insulin-induced and fast-induced) hypoglycemia up-regulates genes for glucose uptake (GLUT1, AGT, ID1, and MKP) in the hypothalamus, thereby preserving the brain's need for glucose, and it also down-regulates the counterregulatory response (53,54). This phenomenon could be part of the explanation for the large number of asymptomatic hypoglycemias.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%